Aurintricarboxylic Acid Reduces Platelet Deposition in Stenosed and Endothelially Injured Rabbit Carotid Arteries more Effectively than other Antiplatelet Interventions - Golino, Palolo; Ragni, Massimo; Cirillo, Plinio; Pascucci, Immacolata; Ezekowitz, Michael D; Pawashe, Aruna; Scognamiglio, Annalisa; Pace, Leonardo; Guarino, Angela; Chiariello, Massimo (Thrombosis and Haemostasis, 1995)
In the present study we tested the effects of different antithrombotic interventions on platelet deposition in experimentally-stenotic rabbit carotid arteries with endothelial injury. Platelet deposition, quantitated by labeling autologous platelets with 111 In-oxine, was significantly reduced compared to control animals by all interventions tested, i.e., R 68070, a drug with thromboxane A2 synthase and receptor blocking properties, BN 52021, a PAF receptor antagonist, aurintricarboxylic acid (ATA), an inhibitor of platelet glycoprotein (Gp) Ib/von Wille-brand factor (vWf) interaction, AZ-1, a monoclonal antibody against rabbit GPIIb/IIIa, the platelet receptor for fibrinogen, and AP-1, a monoclonal antibody against rabbit tissue factor. ATA was significantly more effective than all the other interventions in reducing platelet deposition in the stenotic vessels. We conclude that inhibition of Gp Ib/vWf interaction may be a more suitable target for antithrombotic therapy under conditions of high shear stress, like those produced in this model.